2022
DOI: 10.21037/apm-21-2171
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cytokine levels and their predictive value in critical patients after major abdominal surgery: a retrospective cohort study

Abstract: Background: It remains uncertain as to what impact cytokine expression level has on patient outcomes.The association of serum levels of interleukin-1β (IL-1β), IL-2, IL-6, IL-8, IL-10, tumor necrosis factor-α (TNF-α), and procalcitonin with critically ill patient outcomes after major abdominal surgery still need to be explored. Methods:From January 1, 2018 to June 30, 2019, a retrospective cohort study was conducted on patients admitted to the surgical intensive care unit (SICU). Levels of IL-1β, IL-2, IL-6, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
1
0
3
Order By: Relevance
“…Low preoperative SMI was also correlated with postoperative complications in patients with pancreatic cancer (14,15). Previous studies have suggested that SMI reduction is associated with increases in the concentration of circulating inflammatory cytokines and with high complication rates (16,17).…”
Section: Discussionmentioning
confidence: 85%
“…Low preoperative SMI was also correlated with postoperative complications in patients with pancreatic cancer (14,15). Previous studies have suggested that SMI reduction is associated with increases in the concentration of circulating inflammatory cytokines and with high complication rates (16,17).…”
Section: Discussionmentioning
confidence: 85%
“…Critical illness is related to metabolic and inflammatory disorders (48). Postoperative serum IL-1b levels are associated with mortality in critically ill patients after major abdominal surgery (49). In addition, it has been shown that IL-1b inhibits thyroid hormone receptor-b1 gene expression (50), which inhibits hepatic D1 expression (51).…”
Section: Discussionmentioning
confidence: 99%
“…Critical illness has been shown to be associated with disturbed metabolic and inflammatory responses (17). Interleukin-1b (IL-1b) is a pro-inflammatory cytokine that is higher in non-survivors than in critically surviving patients (18). Other studies have shown that IL-1b can cause damage or apoptosis of thyroid follicular cells and promote the onset of autoimmune thyroiditis (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Як було показано в дослідженнях Yan Y. та співавт., TNF-α, що виробляється активованими макрофагами, бере участь у системній запальній реакції організму, і рівень його експресії швидко збільшувався після травми [13]. При цьому високі рівні цитокінів безпосередньо пов'язані з рівнем післяопераційної летальності, а високий рівень IL-6 був фактором ризику повторної госпіталізації у відділення інтенсивної терапії у пацієнтів у критичному стані, які перенесли великі абдомінальні операції [13]. До того ж, стресова реакція може спричинити метаболічні та ендокринні порушення, які є фактором ризику масивної кровотечі та інфекції [14].…”
Section: обговорення отриманих результатівunclassified